2015
DOI: 10.4236/msce.2015.39006
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of CuO-Ta<SUB>2</SUB>O<SUB>5</SUB> Composites Using a Simple Co-Sputtering Method

Abstract: We prepared CuO-Ta2O5 composite films using our simple co-sputtering method for the first time. Four specimens were prepared from an as-deposited CuO-Ta2O5 sample by cutting it using a diamond-wire saw, and the specimens were subsequently annealed at 600˚C-900˚C. The X-ray diffraction and photoluminescence (PL) of the annealed specimens were evaluated. The CuO-Ta2O5 film annealed at 600˚C seemed to be primarily amorphous phase, and a sharp PL peak at a wavelength of 450 nm, due to the existence of Cu 2+ , was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…A similar PL peak at λ ~ 450 nm have already been observed only from an amorphous CuO-Ta 2 O 5 film annealed at 600˚C in our previous work [23]. The peak seemed to be attributed to the transition from the conduction band of Ta 2 O 5 to the t 2 energy level of Cu 2+ in the bang gap of Ta 2 O 5 [19] [21] [23]. However, as mentioned above, the presented CuO-Ta 2 O 5 films annealed at 900˚C -1100˚C seemed to be not amorphous but partially Cu 2.1 (Ta 4 O 12 ) crystal phases.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…A similar PL peak at λ ~ 450 nm have already been observed only from an amorphous CuO-Ta 2 O 5 film annealed at 600˚C in our previous work [23]. The peak seemed to be attributed to the transition from the conduction band of Ta 2 O 5 to the t 2 energy level of Cu 2+ in the bang gap of Ta 2 O 5 [19] [21] [23]. However, as mentioned above, the presented CuO-Ta 2 O 5 films annealed at 900˚C -1100˚C seemed to be not amorphous but partially Cu 2.1 (Ta 4 O 12 ) crystal phases.…”
Section: Resultssupporting
confidence: 86%
“…However, as mentioned above, the presented CuO-Ta 2 O 5 films annealed at 900˚C -1100˚C seemed to be not amorphous but partially Cu 2.1 (Ta 4 O 12 ) crystal phases. The origin of the sharp PL peaks presented in Figure 2 may be different from that reported in [23]. In addition, we have reported that CuO-Ta 2 O 5 films prepared using a CuO pellet become tetragonal CuTa 2 O 6 phases after annealing at 700˚C -900˚C, and no sharp PL peak was observed from the films [23].…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Furthermore, four significant peaks were additionally observed from the specimens annealed at 900˚C and 1000˚C in addition to the peaks corresponding to the above-mentioned (2 0 0) (hexagonal Ta PL peak was observed from all the specimens. In our previous report, we found that the CuO-Ta 2 O 5 composite films annealed at 700˚C -900˚C were tetragonal CuTa 2 O 6 phases, and we considered that our CuTa 2 O 6 film annealed at 900˚C had almost no defect because broad PL peaks due to oxygen-vacancy trap levels were not observed [19]. Therefore, it seems that our Cr 2 O 3 -Ta 2 O 5 composite films also have almost no defect because no significant PL peak was observed from the films as presented in Figure 3.…”
Section: Resultsmentioning
confidence: 96%
“…It can be widely applicable to various passive/active optoelectronics elements such as anti-reflection coatings for silicon solar cells [1], photonic crystals fabricated using the autocloning method [2] [3], and novel phosphors doped with rare-earths [4]. We have so far prepared various rareearth (Er, Eu, Yb, Tm, Y, and Ce) doped Ta 2 O 5 thin films using radio-frequency (RF) magnetron co-sputtering of rare-earth oxide (Er 2 Furthermore, we have also prepared copper (II) oxide (CuO) and Ta 2 O 5 co-sputtered (CuO-Ta 2 O 5 ) films using the same co-sputtering method, and we have evaluated X-ray diffraction (XRD) and PL properties of the films after annealing [19]. We find that our CuO-Ta 2 O 5 composite films annealed above 700˚C can be tetragonal CuTa 2 O 6 phases, and good-quality CuTa 2 O 6 films with almost no defect can be obtained using our co-sputtering method and subsequent annealing above 900˚C.…”
Section: Introductionmentioning
confidence: 99%